(untitled) (Research, Society and Development, 2022)
This retrospective epidemiological study aims to describe the confirmed cases of this disease in northeastern Brazil in the period 2010-2019. This is an investigative, documentary research with a quantitative descriptive approach, based on secondary data collection, obtained through SINAN. The total number of confirmed cases in Brazil was 7,457, and the Northeast stood out, 19% (1407), however, there was a significant increase in cases in recent years, 2018 of 127.4% and 2019 of 50%, in relation to the previous year of 2017. Regarding the notification of cases, Piauí reported the highest rate in total, with 30.3%. The population aged 20-39 years (56.6%) was more susceptible, moreover, regarding gender, males presented greater vulnerability to the risk of infection. The cases confirmed according to race, brown color was prevalent, 70% (985) in all. As for diversity, P. vivax 67% (943) followed by P. falciparum 25.6% (361), showed prevalence in all regions, however, it was observed that Piauí 77% (276) had the highest number of cases of notification for the combination of these two species in this period. In this perspective, given the number of cases in this region, it is not possible to raise awareness about the preventive use of antimalarials related to emigration in non-endemic regions and more epidemiological research is required, since its notoriety is still low.